Generic drugs: a study on awareness among medical students and interns - C. R., Manasa; L., Kalpana; R. M., Veena (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Use of generic drugs and its availability is one of the less discussed topics in the medical education but at the same time holds a lot of importance in providing affordable health care to the general public. Methods: All 150 II MBBS students and 80 interns who were willing were included in the study. After explaining the aims and objectives and obtaining the informed consent, a set of 14 semi structured questionnaire were given to the students through an online link. A total duration of 15 minutes was given to complete the questionnaire and submit to prevent bias. Results: Most of the students 98 (75.4%) believe that generic drugs are non-inferior to branded drugs compared to interns 33 (49.3%) who are still doubtful about its efficacy (p=0.0003). Most of the students 101 (77.7%) and interns 52 (77.6%) think that composition, dose and indications are same as branded drugs (p=0.987). 75 (57.7%) students and 25 (37.3%) of interns know that generic medicines are marketed only after the expiry of patent period of innovator drug (p=0.005). About 102 (78.5%) students and 44 (65.7%) interns prefer to prescribe generic drugs to their patients (p=0.061). Only 34 (26.2%) students and few interns 19 (28.4%) knew about jan aushadhi sugam app (p=0.744). Conclusions: Lack of awareness about the jan aushadhi sugam app and location of nearby generic stores was acting as the main hindrance in optimal utilization of generic drugs.